Convexity subarachnoid hemorrhage in lobar intracerebral hemorrhage: A prognostic marker - Raposo, Nicolas (Neurology, 2020)
OBJECTIVE: To investigate whether acute convexity subarachnoid hemorrhage (cSAH) associated with acute lobar intracerebral hemorrhage (ICH) increases the risk of ICH recurrence in patients with cerebral amyloid angiopathy (CAA). METHODS: We analyzed data from a prospective cohort of consecutive survivors of acute spontaneous lobar ICH fulfilling the Boston criteria for possible or probable CAA (CAA-ICH). We analyzed baseline clinical and MRI data, including cSAH (categorized as adjacent or remote from ICH on a standardized scale), cortical superficial siderosis (cSS), and other CAA MRI markers. Multivariable Cox regression models were used to assess the association between cSAH and recurrent symptomatic ICH during follow-up. RESULTS: We included 261 CAA-ICH survivors (mean age 76.2 ± 8.7 years). Of them, 166 (63.6%, 95% confidence interval [CI] 57.7%–69.5%) had cSAH on baseline MRI. During a median follow-up of 28.3 (interquartile range 7.2–57.0) months, 54 (20.7%) patients experienced a recurrent lobar ICH. In Cox regression, any cSAH, adjacent cSAH, and remote cSAH were independent predictors of recurrent ICH after adjustment for other confounders, including cSS. Incidence rate of recurrent ICH in patients with cSAH was 9.9 per 100 person-years (95% CI 7.3–13.0) compared with 1.2 per 100 person-years (95% CI 0.3–3.2) in those without cSAH (adjusted hazard ratio 7.5, 95% CI 2.6–21.1). CONCLUSION: In patients with CAA-related acute ICH, cSAH (adjacent or remote from lobar ICH) is commonly observed and heralds an increased risk of recurrent ICH. cSAH may help stratify bleeding risk and should be assessed along with cSS for prognosis and clinical management.